Impact of COVID-19 on community health: A systematic review of a population of 82 million - Sathian, Brijesh; Asim, Mohammad; Mekkodathil, Ahammed; van Teijlingen, Edwin R.; Subramanya, Supram Hosuru; Simkhada, Padam; Marahatta, Sujan Babu; Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2020)
The novel coronavirus disease 2019 (COVID-19) outbreak, caused by the pathogenic severe acute respiratory syndrome-2 (SARS-CoV-2) virus, is exponentially spreading across the globe. As there is paucity of published literature, the influence of COVID-19 on community health remains unclear. Therefore, we aimed to conduct a systematic review of the literature on the impact of COVID-19 on community health. The current systematic review was performed utilizing electronic databases, i.e., PubMed, MEDLINE, and EMBASE. We searched for the keywords "COVID-19" AND "community health" between January 1, 2020, until May 10, 2020. Although, limited evidence is available regarding quarantine to prevent COVID‐19, most studies considered quarantine as an essential public health measure to minimize rate of infection and mortality. Under these circumstances, people should focus on maintaining personal hygiene, proper nutrition, and extreme social distancing to reduce the risk of COVID-19. Besides, that there is a need to provide professional psychological support to reduce mental ill-health. We have highlighted two different public health approaches in South Asian countries, namely Nepal and India.